Forgiveness and Interpersonal Problem Solving : Mediating Role of Personality - Chauhan, Mitali (Thapar Institute of Engineering and Technology, 2025)
The present research sought to explore the mediating role of personality in the relationship between forgiveness and interpersonal problem-solving. This cross-sectional, correlational study involved a sample of 100 students aged 18 to 30 from four universities in Punjab. The data was collected by using standardized instruments such as Bolton Forgiveness Scale, the Big Five Inventory, and the Short Form of the Social Problem Solving Inventory. Correlational analysis and regression indicated a positive association between forgiveness and adaptive problem-solving styles (including positive problem orientation and rational problem solving) as well as with personality traits like agreeableness, extraversion and openness. Mediation analysis using Hayes’ PROCESS macro revealed that agreeableness and openness partially mediated the relationship between forgiveness and interpersonal problem solving (constructive problem solving). Neuroticism was associated with maladaptive strategies such as impulsive carelessness and negative problem orientation. The results suggest that forgiveness serves as an important emotional resource that facilitates improved interpersonal functioning and conflict resolution through the influence of personality traits. Keywords: Forgiveness, Interpersonal Problem Solving, Personality, Big Five Model.
Keywords: Forgiveness; Interpersonal Problem Solving; Mediating Role of Personality; Big Five Model; Methodology; Review of Literature